Efektivitas Pemanfaatan Sumber Pembiayaan Pendidikan Di SMA Ta’miriyah Surabaya - Nadia Salsabila (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
Financing is an important component in providing education. Education costs are the amount of money generated and spent on various educational equipment which includes teacher salaries, facilities and infrastructure, administrative activities, education management activities, procurement of tools and textbooks, extracurricular activities and so on. This study aims to determine the effectiveness of utilizing financing sources in Ta'miriyah High School Surabaya. This study used a descriptive qualitative approach. Data collection techniques are carried out by interviews and observations. Financing is the most crucial thing that must be faced by education providers. In order for educational goals to be achieved, the management of education funds must be carried out properly and appropriately. This research was held at Ta'miriyah High School Surabaya, because researchers wanted to know the sources of education financing in private schools and their utilization. The results showed that the utilization of funding sources for Ta'miriyah High School Surabaya, both from School Operational Assistance funds, Operational Support Costs for Education Implementation, and Education Development Contribution funds were quite effective both in terms of personnel and non-personnel